The Acute Toxicity of Rutin in Mice - Sahib, Hayder B; Muhammad Hamid, Zeena (Iraqi Journal of Pharmaceutical Sciences, 2021)
Acute toxicity is a step to evaluate the toxicity of a substance. Rutin is one of the flavonoid compounds with a variety of pharmacological effects. The aim of the study is to calculate the lethal dose that affect fifty percent of the mice used in the experiment (LD50). Thirty Swiss albino male and 30 non-pregnant female mice have been divided equally and randomly into 5 treated groups and one control group (n=5) Rutin has been administered with concentrations 5, 2.5.1.25,0.625 and 0.312 g/kg administered as a single dose intraperitoneally (IP) while the control group received 1% DMSO (IP). Animals were observed for any morbidity and mortality for 14 days. After 14 days the animal blood collected for biochemical and hematological analysis then all animals are euthanized for histopathological evaluation. The results showed the LD50 was 1.51 g/kg for male mice while for female mice was1.49 g/kg. No significant changes were observed at dose of 1.25glkg (female) and 0.625, 0.312 glkg (both sexes) in body weight measurements and in biochemical or hematological assays. Moreover no significant histopathological changes were reported compared to control.. It can be concluded that Rutin is practically a non-toxic substance.